2006
DOI: 10.13031/2013.20447
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Producing Fuel Pellets From Biomass

Abstract: An engineering economic analysis of a biomass pelleting process was performed for conditions in North America. The pelletization of biomass consists of a series of unit operations: drying, size reduction, densifying, cooling, screening, and warehousing. Capital and operating cost of the pelleting plant was estimated at several plant capacities. Pellet production cost for a base case plant capacity of 6 t/h was about $51/t of pellets. Raw material cost was the largest cost element of the total pellet production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(157 citation statements)
references
References 11 publications
4
149
0
4
Order By: Relevance
“…The first constraint requires that there should be enough biomass collected to produce the pellets corresponding to the annual heat demand of the customers, plus the extra amount of biomass required as a fuel source to perform the drying process during pelleting. Mani et al (2006) have examined the effect of various fuel options for the drying process and concluded that the most cost-efficient method is to use wet biomass, which is in line with the assumption made here:…”
Section: Objective Functionsupporting
confidence: 72%
See 1 more Smart Citation
“…The first constraint requires that there should be enough biomass collected to produce the pellets corresponding to the annual heat demand of the customers, plus the extra amount of biomass required as a fuel source to perform the drying process during pelleting. Mani et al (2006) have examined the effect of various fuel options for the drying process and concluded that the most cost-efficient method is to use wet biomass, which is in line with the assumption made here:…”
Section: Objective Functionsupporting
confidence: 72%
“…In the work of Sultana et al (2010) a thorough analysis was performed, the cost structure was split in discrete components and the cost break-down was analyzed for different agricultural biomass pellet types and plant capacities. Mani et al (2006) focused on wood pellets but also investigated the feasibility of alternative fuels for drying the wet biomass before the pelleting process. Thek and Obernberger (2004) carried out a detailed study of sawdust pellet production in a European plant.…”
Section: Pellet Productionmentioning
confidence: 99%
“…The images showed only the entanglement of particles in pellets made from timothy hay and switchgrass. This might provide evidence that the lignin content in the biomass is responsible for the mechanical properties of the pellet [28]. Pressure, temperature, and moisture promote adhesion by bonding with a solid bridge between particles.…”
Section: Fracture Analysis Of Forestry and Agricultural Biomass Pelletmentioning
confidence: 97%
“…Smaller particles can encourage the particles to bind and compact, as this requires a lower amount of work ( Figure 4) to yield quality pellets as compared to larger particles. The particle bonding in RCG (Figure 5b) is most likely due to the combination of particle entanglement and auto-adhesive surfaces [26,28].…”
Section: Work Needed To Pelletize Biomass and Blended Biomasses (50:50)mentioning
confidence: 99%
“…Densification of cellulosic biomass into pellets [13] can increase the bulk density from 40 to 250 kg/m 3 for cellulosic biomass materials to as high as 1200 kg/m 3 [14].…”
Section: Introductionmentioning
confidence: 99%